Non-adherence to life-style modification and its factors among type 2 diabetic patients - Shirin Jahan Mumu; Farzana Saleh; Ferdous Ara; Fadia Afnan; Liaquat Ali (Wolters Kluwer Medknow Publications, 2014)
Non-adherence to preventive and therapeutic life-style recommendations among patients with diabetes is special challenge in the management of these patients. This study aimed to measure the proportion of non-adherence to life-style modification and factors associated with these among a group of Bangladeshi type 2 diabetic patients. Under an analytical cross-sectional design 374 type 2 diabetic patients (age >20 years), diagnosed for at least 1 year, were selected from different health care centers operated by the Diabetic Association of Bangladesh. Non-adherence rate were assessed for: Diet (88%), exercise (25%), routine blood glucose testing (32%), foot care (70%), smoking (6%) and betel quid chewing habit (25%). Binary logistic regression suggests that higher education group (P = 0.013), rural area (P = 0.013) and attendance to diabetes education classes (P = 0.043) showed good adherence to diet and non-attendance to diabetes education class (P = 0.014), older age (P = 0.037) are associated to non-adherence to exercise. Unemployed patients showed more non-adherence to blood glucose testing (P = 0.045) than others. Non-attendance to diabetes education class (P = 0.037) and business occupation group (P = 0.039) showed significant association to smoking and betel quid intake habit respectively.